Job Anxiety and Occupational Stress among Employees of IT Sector: Impact on their Attitude towards Management - Kamal Karamchandani; Dr. V. K. Dubule (International Journal of Engineering and Management Research, 2020)
Information technology is the fastest growing sector in the country and the highest employer in the private sector. The fast-paced technological changes, the need to keep up with it and the huge workload puts enormous demands on the employees. They experience anxiety and stress at the workplace which affects, positively and negatively, their attitude towards their job and management. Hence, the study investigated the relationship between anxiety and stress experienced by the employees at the workplace and how each factor affects their attitude towards their management respectively. Since the study covered both male and female employees, hence similar nature of relationship between the variables was also examined separately for each gender For this ex-post facto research, a convenience sample of 200 respondents through stratified sampling technique was chosen in 2019 from various IT firms in Hyderabad. The age of the respondents was between 24-36 years. The data for analysis was collected through 3 scales/ index viz. 1) Job Anxiety Scale by Dr. A. K. Srivastava 2) Occupational Stress Index by A K Srivastav and A P Singh 3) Attitude Scale for Measuring Employee Attitude Towards Management Attitude Scale for Measuring Employee Attitude Towards Management by Dr. K D Kapoor and a personal information sheet. Statistical tools of Pearson was applied to analyse the data. The results of the study confirmed that occupational stress significantly and negatively predicted attitude towards management of the employees. But, on the contrary for job anxiety the relationship with employee attitude was found to be insignificant. The attitude towards management of female employees was found to be more significantly and negatively related to job anxiety and occupational stress respectively as compared to their male counterparts. This result belied the expectations. However, no interaction effect was observed between job anxiety and occupational stress while predicting attitude towards management. It is recommended that IT companies must design general and gender based intervention strategies to reduce job anxiety and occupational stress among employees.